Deoxynivalenol in food and feed: Recent advances in decontamination strategies - Li, Yingfeng; Gao, Huihui; Wang, Ru; Xu, Qing (Frontiers in Microbiology, 2023)
Deoxynivalenol (DON) is a mycotoxin found worldwide that mainly contaminates animal feed and crops. DON not only causes significant economic losses, but also diarrhea, vomiting, and gastrointestinal inflammation in humans and animals. Thus, there is an urgent need to find efficient approaches for DON decontamination in feed and food. Physical and chemical treatment of DON may affect the nutrients, safety, and palatability of food. In contrast, biological detoxification methods based on microbial strains or enzymes have the advantages of high specificity, high efficiency, and nontoxic metabolism. In this review, we comprehensively summarize the recently developed strategies for DON detoxification and classify the mechanisms whereby DON is detoxified. In addition, we identify remaining challenges in DON biodegradation research and suggest research directions to address them. In the future, an in-depth understanding of the specific mechanisms whereby DON is detoxified will provide an efficient, safe, and economical means for the removal of toxins from grains and feed.